Études criminologiques et psychiatriques au Japon - Yoshimasu, Shufu; Kogi, Sadakata (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1969)
AbstractCRIMINOLOGICAL AND PSYCHIATRIC STUDIES IN JAPAN Criminological development in Japan is largely the work of the Japanese Association of Criminology, founded in Tokyo in 1913. The year 1935 saw the debut of the publication Acta criminologia?: et medicinee legalis japonica. After an interruption of several years caused by the second world war, society made great strides, and important research could then be undertaken. There are now three State institutes of criminology in Japan: the General Research Institute of Forensic Medicine at the Tokyo University of Medicine and Dentistry, the Institute of Research, Practical and Clinical Training at the Ministry of Justice, and the Institute of Encephalographie Research of the University of Tokyo. Among the most important criminological and psychiatric research projects are: 1) Study of twins: Led by Yoshimasu, this could be considered as one of the most brilliant contributions of Japanese criminology to science. It is based on the rate of concordance between homozygotic and heterozygotic twins. For a clearer understanding of the phenomenon of concordance between the two partners, Yoshimasu used the following factors: age at first offence, age at the time of research, and number of relapses. The results of his analysis show a lesser rate of agreement than that of foreign studies, nevertheless this rate increased perceptibly after the second world war, which is explained by the influence of environment. 2) Research on recidivism by means of analysis of the life curve: In 1951, Yoshimasu discovered a new method for analyzing the criminal careers of recidivists (this method is defined in English as «the criminal life curve» and in German, die kriminelle Lebenskurve). It comprises three indices: a) age at the time of first offence: before or after 25 years; b) the type of offence: classified in accordance with the kind of crime, the sequence of crime and the kinds of crimes committed during any one episode, i.e. one, the same or different; c) interval between the offences: sequence, remission, intermission, suspension. Later on, various studies were added to this research. 3) Characteristics of various crimes: The studies undertaken dealt with homicidal women, homicidal girls, mass murderers (Massenmo'rder). These studies showed interesting results, because there is an intimate relationship between patricide and the family environment in the traditional Japanese atmosphere. Other researchers were interested in arsonists, sex criminals, persistent embezzlers, recidivists in crimes of violence. 4) Research on juvenile delinquency: In this field, Japan may well be proud of having several pioneers. We stressed the importance of the psychopathic personality, as much as the sheer asymmetry of psychic and physical maturity. 5) Criminality of the mentally disturbed with encephalitis due to anti-rabies vaccination: Studies undertaken after the massacre of 12 employees of the Teikoku Bank of Tokyo revealed that subjects suffering from this malady have a deviated personality of a mythomanie type with Korsakov's syndrome. Other studies show a seat of demyelinized fibres. Treatment could thus be applied to effectively fight this illness. 6) Amphetamine drug addiction and criminality: This problem took on the dimensions of a national crisis after the second world war, when amphetamine drug addiction rose to 200 000. The work undertaken on this problem revealed psychopathic personalities characterized by hyperthymic tendencies, hysterics, explosiveness or instability, as explained by Kurt Schneider. 7) Reactions to penal institutions and disciplinary infractions: With regard to these, a new method called infractiologie was used. It is concerned with the actual relationship which exists between crimes committed in society and infractions committed within the penal institution.